The moral intelligence of children [soundrecording] - Coles, Robert (Audio Renaissance Tapes, 1997)
Describes how a moral intelligence is enable through the moral imagination that is our gradually developed capacity to reflect what is right and wrong with all the emotional and intellectual sources of the human mind. Describes also how conversations, looks moves and witnessing the behavior of others can foster inner spiritual growth.